Effect of Phototherapy on Serum Calcium Level in neonatal hyperbilirubinemia - Shrestha, Sandeep; Budhathoki, Sunil; Sanjel, Seshananda; Sindan, Namrata; Kayastha, Nirajana; Shrestha, Annie (Journal of Karnali Academy of Health Sciences, 2021)
Background: Neonatal hyperbilirubinaemia or jaundice is most common morbidity seen in first week of life. Approximately 60% of term and 80% of preterm newborn develop clinical jaundice. Phototherapy is one of the therapy methods for jaundice. It has few side effects, one of them is hypocalcemia. This study was done to see the effect of phototherapy on serum calcium level on jaundiced neonates.Methods: This was a prospective cross-sectional study, conducted from May 2020 to April 2021 at the Neonatal Intensive Care Unit and Special Newborn Care Unit of Karnali Academy of Health Sciences (KAHS), Jumla. A total of 40 neonates either male or female who had jaundice and placed under phototherapy were enrolled for this study. Blood sample for total serum bilirubin levels and serum calcium levels were sent. They were measured before starting and after stoppage of phototherapy. All the data were recorded in the preformed proforma. It was then, analyzed with the help of SPSS version 16. p-value< 0.05 was considered statistically significant.Results: The mean age and mean gestational age of the neonates was found to be 4.12±1.09 days and 38.55 ± 2.34 weeks respectively. The mean age at which jaundice was noticed in the neonates was 4.13 ± 1.4 days. Pre-phototherapy and post phototherapy level of total serum bilirubin was 14.53 mg/dl ± 2.91 mg/dl and 10.29 mg/dl ± 2.13 mg/dl respectively whereas serum calcium level before and after initiating phototherapy was 9.23 ± 1.11 mg/dl and 8.37 ± 0.69 mg/dl respectively. Hypocalcemia was found in 22.5% of jaundiced neonates receiving phototherapy.Conclusions: Phototherapy which is the mainstay of treating hyperbilirubinemia in neonates decreases serum calcium level in jaundiced neonates.